103 butterflies (Papilionoidea) from Ilha Grande and Ilha da Marambaia, Rio de Janeiro, Brazil - Pinheiro, Carlos Eduardo Guimarães; Ribeiro, Millena Castro; Xerez, Roberto de (Arquivos de Zoologia, 2021)
Here we show a list of 103 butterflies (Papilionoidea) found at Ilha Grande and Ilha da Marambaia, Rio de Janeiro State, Brazil. To our knowledge, this is the first butterfly inventory conducted in these islands. The species richness, the collecting methods utilized, endemism, and the mimicry rings found in the islands are discussed. Moreover, we emphasize the importance and the utilization of butterflies as suitable models to assess community ecology patterns.